Wybrane aspekty satysfakcji zawodowej w Polsce i innych krajach Unii Europejskiej - Kwiatkowska-Ciotucha, Dorota; Załuska, Urszula (Some Aspects of Job Related Satisfaction in Poland and Other European Union Countries, 2007)
Authors presented research problems focused on some aspects of job related satisfaction perception. The goal of the paper was identification of differences and similarities in the fields of job satisfaction, especially between Poland and old European Union countries. Two sources of data were used: the data on job related satisfaction contained in the ECHP database (European Community Household Panel) where some 150 thousands respondents from 15 old EU from period 1994-2001 and Polish data form survey research conducted by Pentor Agency in April 2006.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 270-278